Impact of Ultra-Early Perioperative Antihypertensive Therapy in Acute Intracerebral Hemorrhage - Tao Liu; Linan Chen; Leibo Liu; Yang Liu; Lu Ma; Laurent Billot; Qiang Li; Zhihao Zhao; Alejandra Malavera; MUÑOZ VENTURELLI, PAULA ANDREA; Asita de Silva; Huy Thang Nguyen; et al. (Ovid Technologies (Wolters Kluwer Health), 2026)
BACKGROUND: Early intensive blood pressure (BP) lowering improves outcomes in acute intracerebral hemorrhage, but its perioperative benefit among patients undergoing surgical hematoma evacuation is uncertain. We evaluated whether earlier achievement of intensive BP targets is associated with improved outcomes in this population. METHODS: Post hoc secondary analysis of the INTERACT3 (the third Intensive Care Bundle With Blood Pressure Reduction in Acute Cerebral Haemorrhage Trial) pragmatic, international, multicenter, blinded-end point, and stepped-wedge cluster-randomized trial. Among 7036 enrolled intracerebral hemorrhage patients at 121 hospitals, those who underwent surgical hematoma evacuation were included. Patients were categorized by time from hospital arrival to achieving the target systolic BP <140 mm Hg: ≤2 hours versus >2 hours. The primary outcome was 6-month mortality. Key secondary outcomes included death or disability (modified Rankin Scale scores 4–6), modified Rankin Scale score shift, health-related quality-of-life (EuroQol 5-Dimension 3-Level [EQ-5D-3L] domains, visual analog scale, and health utility index), and serious adverse events. Adjusted associations were estimated using Cox, logistic, ordinal logistic, and linear regression models, controlling for age, sex, treatment type, and admission Glasgow Coma Scale. RESULTS: Of 7036 patients with acute intracerebral hemorrhage, 1506 underwent surgical hematoma evacuation (mean [SD] age, 59.7 [11.8] years; 33.9% women). Overall, there was no statistically significant difference in 6-month mortality between patients who achieved target BP within 2 hours of treatment initiation and those who achieved it after 2 hours (adjusted hazard ratio, 0.81 [95% CI, 0.63–1.04]; P =0.09). Early BP achievement was associated with a lower risk of death or disability (adjusted odds ratio [OR], 0.71 [95% CI, 0.56–0.90]; P =0.01), a favorable shift in the distribution of modified Rankin Scale scores (adjusted common OR, 0.73 [95% CI, 0.60–0.89]; P <0.01), and fewer serious adverse events (adjusted OR, 0.73 [95% CI, 0.57–0.94]; P =0.02). EuroQol 5-Dimension 3-Level outcomes also favored the early group, with significant improvements in mobility (adjusted OR, 0.76 [95% CI, 0.60–0.97]; P =0.03), pain/discomfort (adjusted OR, 0.72 [95% CI, 0.54–0.95]; P =0.02), and usual activities (adjusted OR, 0.79 [95% CI, 0.62–1.00]; P =0.05), as well as higher visual analog scale (mean difference, 0.08 [95% CI, 0.002–0.17]; P =0.04) and health utility scores (mean difference, 0.05 [95% CI, 0.02–0.09]; P <0.01). CONCLUSIONS: In patients with intracerebral hemorrhage undergoing surgical hematoma evacuation, perioperative intensive BP reduction appears safe. Achieving systolic BP <140 mm Hg within 2 hours was associated with better functional and quality-of-life outcomes, and fewer serious adverse events. These time-sensitive associations support prioritizing ultra-early perioperative BP control; confirmatory prospective analyses are warranted. REGISTRATION: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03209258.